Metaphors We Work By: Reframing Digital Objects, Significant Properties, and the Design of Digital Preservation Systems - Becker, Christoph (Archivaria, 2018)
Much digital preservation research has evolved around the idea of authentic digital objects and their significant properties. However, the nature of digital preservation work continues to be ill-defined. This paper unpacks definitions of digital objects and their significant properties to deconstruct misleading conflations. I review how the use of the terms digital object and significant properties has evolved in digital preservation, and I identify conceptual inconsistencies. By critiquing the system boundaries assigned by different writers to the term digital objects, I explore the metaphorical nature of the concept and show that the discourse routinely ignores the role of computation in favour of artifact-centred concepts of bits and records. As a consequence, I illustrate category errors around what it means to migrate and preserve digital objects. I suggest a reformulation of both terms based on their metaphorical nature and discuss how this reformulation aligns with insights from research on electronic records and digital preservation. The discussion shows that digital objects are best understood as a metaphorical concept that allows us to articulate the emergent properties of computed performances relying on data, software, and hardware. Significant properties are best understood as mechanisms that allow curators to specify shared understandings of what constitutes authentic reproductions of digital objects. At the core of digital preservation is the design of software-based information systems intended to reproduce authentic digital objects. The article thus contributes to a reframing of the nature of digital preservation and emphasizes the importance of the conceptual frame of computing and systems design in archival education and practice. RÉSUMÉ L’idée des objets numériques authentiques et de leurs propriétés importantes a fait évoluer une grande quantité de recherche portant sur la préservation numérique. Cependant, la nature du travail en préservation numérique n’est toujours pas bien définie. Cet article décortique les définitions des objets numériques et leurs propriétés importantes afin de déconstruire des amalgames trompeurs. J’examine comment l’utilisation des termes objets numériques et propriétés importantes ont évolué en préservation numérique et j’identifie les inconsistances conceptuelles. En critiquant l’attribution de limites de système à la notion d’objet numérique par divers auteurs, j’explore la nature métaphorique du concept et je montre que ce discours ignore couramment le rôle du traitement informatique en faveur de concepts centrés sur l’artéfact tels les bits et le document d’archives. Comme résultat, je dresse les erreurs de catégories dans ce que l’on entend par la migration et la préservation d’objets numériques. Je suggère une reformulation des deux termes en fonction de leur nature métaphorique et je discute de la façon dont cette reformulation s’aligne sur les résultats de la recherche sur les documents numériques et la préservation numérique. Cette discussion démontre que les objets numériques sont davantage compris comme un concept métaphorique permettant d’énoncer les propriétés émergentes des performances de système qui utilisent des données, des logiciels et du matériel informatique. Les propriétés importantes sont davantage comprises comme des mécanismes qui permettent aux conservateurs de préciser les compréhensions communes de ce en quoi consiste la reproduction authentique d’objets numériques. Au coeur de la préservation numérique se trouve la conception de systèmes d’information logiciels qui servent à la reproduction authentique des objets numériques. Cet article contribue alors à la redéfinition de la nature de la préservation numérique et met l’accent sur l’importance d’un cadre conceptuel en matière de traitement informatique et de conception de systèmes d’information dans la formation et la pratique archivistiques.